Civil Engineering 4 Real (CE4R): co-curricular learning for undergraduates. (2nd January 2020) - Murray, Mike; Hendry, Gillian; McQuade, Robert
ABSTRACT: Vocational disciplines such as engineering provide an ideal opportunity for contextualising the curriculum. The provision of co-curricular activities can stimulate students to assimilate their prior knowledge and skills whilst enhancing employability attributes. Team-based co-curricular activities linked to problem-based learning can offer students a quasi-authentic experience of engineering practice. In this paper, we provide a case study of a successful co-curricular initiative supported by local civil engineering employers. Civil Engineering 4 Real (CE 4 R) are evening workshops facilitated by practicing engineers, where student attendance is voluntary. Students use authentic documentation and collaborate in peer learning to solve industrial problems. CE 4 R has assisted student's anticipatory socialisation into their disciplinary profession. However, further research is required to establish the cognitive legacy that students gain from attending CE 4 R. There is also a need to explore the synergy that could be prompted through understanding the boundaries between CE 4 R and the programme curriculum.